2017
DOI: 10.1111/jpc.13610
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal surgery in a developing country: Outcome of co‐ordinated interdisciplinary collaboration

Abstract: Despite the persisting challenges, co-ordinated team management may result in the modest improvement of outcomes of neonatal surgery in our setting. Addressing these challenges may further improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…According to UNICEF child mortality report (2019), neonatal deaths accounted for 47 per cent of all under-five deaths and it has been predicted that 26 million new-borns would die between 2019 and 2030, and 80 per cent of these deaths would occur in Southern Asia and sub-Saharan Africa [8]. Studies showed that the outcome of neonatal surgical conditions in these regions is also dismal [3,7,10,[14][15][16]. This clearly denotes that some babies born in the LMICs are very unfortunate, and had they been born in any developed world, a large portion of them could have led a normal life.…”
Section: Discussionmentioning
confidence: 99%
“…According to UNICEF child mortality report (2019), neonatal deaths accounted for 47 per cent of all under-five deaths and it has been predicted that 26 million new-borns would die between 2019 and 2030, and 80 per cent of these deaths would occur in Southern Asia and sub-Saharan Africa [8]. Studies showed that the outcome of neonatal surgical conditions in these regions is also dismal [3,7,10,[14][15][16]. This clearly denotes that some babies born in the LMICs are very unfortunate, and had they been born in any developed world, a large portion of them could have led a normal life.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm these findings, and we strongly support the implementation of an interdisciplinary approach with pediatric surgery consultation as a part of the initial examination in cases of unclear anogenital findings to improve outcome. 36…”
Section: Time Of Diagnosis and Clinical Findingsmentioning
confidence: 99%
“…Ekenze et al . undertook a QI project focussed on co-ordinating interdisciplinary collaboration to improve neonatal surgery outcomes in Nigeria 81 . The intervention involved short-term neonatal surgery training for the paediatric surgeons, nurses and anaesthetists in Europe and the US followed by MDT training locally upon their return.…”
Section: Introductionmentioning
confidence: 99%